AKSELERASI PERKEMBANGAN ILMU KEISLAMAN (Suatu Analisis Filosofis) - Nelvawita Nelvawita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This paper wants to explain about the acceleration of the development of Islamic science viewed from a philosophical perspective. At least this discussion reveals its development from a socio-historical point of view and its acceleration process. The development of Islamic sciences and the process of acceleration of scholarship in Islam will never stop, because the scientific process itself will develop based on phenomena and various phenomena of world life that still show signs of life. The development of Islamic sciences is essentially a blend of revelation and intellectual thought, where through brilliant thought and courage to interpret the signs given by Allah, human beings are able to formulate various experiences to make and accelerate the development of science.